2018
DOI: 10.1002/pbc.27403
|View full text |Cite
|
Sign up to set email alerts
|

Management of oral mucositis in pediatric patients receiving cancer therapy: A systematic review and meta‐analysis

Abstract: Background One of the most common complications of cancer chemotherapy is oral mucositis (OM). OM affects more than 75% of patients undergoing chemotherapy and represents a significant burden to patients and caregivers. We performed a systematic review and meta­analysis of published studies to investigate the effects of agents and techniques in reducing OM. Procedure This systematic review investigated, critically appraised, and rated the evidence on agents used to manage OM in children undergoing cancer thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 51 publications
1
41
1
3
Order By: Relevance
“…In the analysis of Mozaffari et al [3], including both children and adults, either after auto-or after allo-HCT, impact of palifermin was shown neither on duration and severity of OM nor on occurrence of aGVHD. On the contrary, in the study of children on conventional chemotherapy, palifermin significantly reduced incidence, duration, and severity of mucositis [5]. Findings that palifermin could be a valid therapeutic tool to improve the quality of life of children suffering from leukemia or lymphoma or undergoing HCT were confirmed by other studies [15,34,35,36], although the lack of effect was also documented [7,30,37].…”
Section: Adverse Events Of Paliferminmentioning
confidence: 79%
See 2 more Smart Citations
“…In the analysis of Mozaffari et al [3], including both children and adults, either after auto-or after allo-HCT, impact of palifermin was shown neither on duration and severity of OM nor on occurrence of aGVHD. On the contrary, in the study of children on conventional chemotherapy, palifermin significantly reduced incidence, duration, and severity of mucositis [5]. Findings that palifermin could be a valid therapeutic tool to improve the quality of life of children suffering from leukemia or lymphoma or undergoing HCT were confirmed by other studies [15,34,35,36], although the lack of effect was also documented [7,30,37].…”
Section: Adverse Events Of Paliferminmentioning
confidence: 79%
“…The experience in pediatric setting is much lower: results of two studies carried out after auto-HCT showed lower incidence of grade III/IV° oral mucositis in patients receiving palifermin, although the other outcomes were inconclusive [32,33]. Recently, two metaanalyses on the use of palifermin were published [3,5]. In the analysis of Mozaffari et al [3], including both children and adults, either after auto-or after allo-HCT, impact of palifermin was shown neither on duration and severity of OM nor on occurrence of aGVHD.…”
Section: Adverse Events Of Paliferminmentioning
confidence: 99%
See 1 more Smart Citation
“…OM lesions are characterized by inflammatory, ulcerative, and bleeding areas with painful clinic symptoms that are difficult for treatment with topic or systemic medications [ 10 ]. Commonly, OM manifests clinically 3 to 10 days following the start of chemotherapy; it depends on the kind of cancer and treatment procedure [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…As OM cases are more severe in children, they compromise more rapidly speech, swallowing, oral hygiene and, consequently, delay treatment and increase mortality [ 12 ]. Approximately 80% of children and adolescents manifest OM at some stage of treatment [ 11 ]. For this reason, knowing the factors that may be related to the occurrence, progression, and duration of OM will aid in the development of more effective preventive and therapeutic protocols [ 8 ].…”
Section: Introductionmentioning
confidence: 99%